Oriented PAN/PVDF/PAN laminated nanofiber separator for lithium-ion batteries. Issue 15 (August 2022) - Zheng, Yixiao; Zhou, Rongxin; Zhao, Huanhuan; Ye, Feng; Zhang, Xiangwu; Ge, Yeqian
Electrospun nanofiber separators have excellent properties in terms of large surface area and high porosity, which benefits the rate capability, electrochemical stability, and safety performance of lithium-ion batteries. Herein, a 0°PAN/PVDF/90°PAN-oriented composite nanofiber separator is prepared, which is prepared layer by layer by electrospinning technology and drum orientation collector. The results show that when the rotating speed of the drum is 600 r min −1, the 0°PAN/PVDF/90°PAN-oriented composite nanofiber separator has high porosity (about 85%), improved transverse and longitudinal tensile properties (10.33 MPa and 11.03 MPa, respectively), good dimensional stability at 160°C, and good electrochemical performance (specific charge capacity of 165 mAh g −1 at 0.5C and 142.7 mAh g −1 at 1C, capacity retention of 90% after 100 cycles).